2017
DOI: 10.18203/2394-6040.ijcmph20173327
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility pattern of Staphylococcus aureus in tertiary care hospital, SRMSIMS, Bareilly, U.P.

Abstract: Background: S. aureus has been recognized as continuously challenging the clinicians despite the availability of antibiotics from nearly 70 yrs and emergence of various types of antibiotic resistance mechanisms especially to methicillin and vancomycin, which was the theme of this study. The study was to determine the antibiotic susceptibility of Staphylococcus aureus in Tertiary Care Hospital, SRMSIMS, Bareilly and also to determine the current status of Vancomycin susceptibility in our Hospital setup consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Researchers have also reported varying level of resistance to clindamycin and doxycycline among MRSA. Gupta et al 6 in his studies reported 75.5% of MRSA isolates were resistant to clindamycin and in contrast, Mamtora et al 17 reported 73% of MSSA strains were resistant. In our study 50% of MRSA and 25% of the MSSA strains were resistant to clindamycin.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Researchers have also reported varying level of resistance to clindamycin and doxycycline among MRSA. Gupta et al 6 in his studies reported 75.5% of MRSA isolates were resistant to clindamycin and in contrast, Mamtora et al 17 reported 73% of MSSA strains were resistant. In our study 50% of MRSA and 25% of the MSSA strains were resistant to clindamycin.…”
Section: Discussionmentioning
confidence: 95%
“…Data on the prevalence of MRSA is not uniform. Literature has documented a significant variation in the prevalence rate from different parts of India and between countries [1][2][3][4][5][6][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] . Studies from India report MRSA prevalence ranging from 6.9% to 87% 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many other researchers have also reported resistance to ciprofloxacin (70-80%) followed by erythromycin (60-80%), trimethoprim/sulfamethoxazole and/or cotrimoxazole (60-80%) and 50-70% resistance to gentamicin. 14 Resistance to penicillin is documented by Gupta et al (2017) and Mehta et al (2017). 22,23 Similarly, Dat et al (2017) has documented 100% sensitivity to vancomycin and linezolid, as given in our study.…”
Section: Discussionmentioning
confidence: 99%
“…14 Resistance to penicillin is documented by Gupta et al (2017) and Mehta et al (2017). 22,23 Similarly, Dat et al (2017) has documented 100% sensitivity to vancomycin and linezolid, as given in our study. 24 All these findings are equally in comparison with our study.…”
Section: Discussionmentioning
confidence: 99%